Theoretical Genealogy of Inner-city Highways and Analyzing Its Impacts on Surroundings - Mohammad soleimani; Ahmad zanganeh; Taher parizadi; gholamhosein jahandar (تحقیقات کاربردی علوم جغرافیایی)
Urban highways, as one of the most important sectors of transportation, have always been one of the most challenging, both in terms of budget consumption and its spatial, social, economic and environmental impacts on the city. It has been urban elements. To this end, this study analyzes the impacts of inter-city highways, examines the theories of how to deal with this spatial element, as well as the factors involved. The type of research is applied-theoretical and the method is documentary-analytical. The sources of information used in this research are all documents, documents, books, articles, plans, and scientific research on urban highways. The results indicate that there are favorable and disagreeable views and views on the creation of inter-city highways. Modernist thinkers and urban engineers, advocates of urban highways, and later urban planners and geographers, are opposed to one-dimensional attention to these highways and inner-city development relying on highways. The results also showed that the inter-city highways had social, economic, physical and environmental impacts and, depending on the location conditions and the socio-economic characteristics of the location, these impacts were positive and negative in space. It looks around.